Integration of the equity markets in the CEE countries - opportunity for international portfolio diversification - Krutišová, Alena; Klosová, Anna, 1942-; Jegers, Marc; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2011)
There are several advantages of capital markets integration, such as increasing overall market liquidity, improving the scope for diversification and risk sharing. Therefore, the European institutions try to boost capital markets integration among the member states. The aim of this empirical paper is to analyse the level of integration of the main equity markets in the Central and Eastern Europe (CEE): the Czech Republic, Poland, Hungary, Slovakia, Romania and Bulgaria from 2001 until 2010 using an integration score analysis. This methodology was proposed by Akdogan (1996; 1997) and later extended by Barari (2004) and by Birg & Lucey (2006). The paper focuses on the developments of regional and global integration of these countries. Findings from this research can be of interest to investors as well as policy makers because the degree of capital markets integration has important implications for cross-border capital flows, financial management, and for the conduct of monetary policy. The results from this paper suggest that the opportunities for portfolio diversification are diminishing in the CEE countries. The diversification benefits were mainly reduced by the accession to the EU, but they did not completely disappear. The findings showed that the global financial crisis in 2008 brought about a rapid change in integration. Global integration increased during the crises, whereas the regional started to decline after years of rising.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of international trade and european integration [obor dipl. práce]